Desalination system using waste heat of power plant - Aybar, HS (Elsevier Science Bv, 2004)
North Cyprus is one of the Mediterranean countries that is suffering from a water shortage because fresh water resources are limited. Currently, the limited resource of water in Northern Cyprus should be used appropriately and saved. The power plants are one part of industry that need a lot of water. The daily total water requirement of a power plant is about 250-300 tons. The water that is taken out from the boiler is at boiler pressure (6 MPa) and at saturation temperature. The fresh water can be obtained using the energy of this wastewater by desalination, and it will be used as fresh make-up water for the power plant. This simple MED system can supply 83% of the water required by the power plant.
3rd Conference on Desalination Strategies in South Mediterranean Countries -- MAY 30-JUN 03, 2004 -- Marrakech, MOROCCO
Keywords: desalination; multi-effect desalination